2020
DOI: 10.1080/17458080.2020.1785621
|View full text |Cite
|
Sign up to set email alerts
|

Investigating folate-conjugated combinatorial drug loaded ZnO nanoparticles for improved efficacy on nasopharyngeal carcinoma cell lines

Abstract: Zinc oxide (ZnO) nanoparticles, due to their well-defined physicochemical and antimicrobial attributes have been presented lately as favourable theranostic nanoplatforms for drug delivery. We hypothesized that surface modification of ZnO nanoparticle with activated polyethylene glycol and folic acid might be of great importance in targeted drug delivery in nasopharyngeal carcinoma since carcinoma cells possess folate receptors absent in normal cells. Therefore in this study, we have prepared and characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Folic acid (FA) as a targeting moiety has been widely investigated in cancer therapy to enhance accumulation and cytotoxicity of nanoparticles towards tumor cells [21,22]. It has been found that FA receptors highly expressed in malignant cells, including TNBC compared to their normal counterparts [23].…”
Section: Introductionmentioning
confidence: 99%
“…Folic acid (FA) as a targeting moiety has been widely investigated in cancer therapy to enhance accumulation and cytotoxicity of nanoparticles towards tumor cells [21,22]. It has been found that FA receptors highly expressed in malignant cells, including TNBC compared to their normal counterparts [23].…”
Section: Introductionmentioning
confidence: 99%